GSI Research Informs Gender and Climate Policy and Submissions through the Africa Group of Negotiators Expert Support (AGNES) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
GSI collaboration with AGNES has resulted in policy submissions to the UNFCCC as well as progress in integrating gender into climate policy at the national level in Sub-Saharan Africa. One gender and climate policy has been completed (Nigeria) and 4 are in progress or expected to be initiated in 2021.